Pendampingan Penambahan Varian Rasa Sebagai Upaya Peningkatan Nilai Jual Produk UMKM Keripik Tempe “Nadhira” - Aan Zainal Muttaqin; Arista Eka Lestiana; Nala Rohmatul Aza (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
The Covid-19 pandemic has significantly impacted the income of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, prompting business actors to adapt through innovation, particularly in product variations. This study aims to enhance the marketability of "Nadhira" Tempe Chips products through strategies of adding flavor variations. The methods employed include interviews, discussions, and hands-on practices in product processing. The results indicate that the implementation of attractive lthe addition of flavor variations can enhance product appeal and increase sales turnover. Business actors also demonstrated a better understanding of the importance of product innovation. The implications of this research highlight the necessity for continuous innovation and market research to maintain product relevance amid changing consumer preferences, as well as providing insights for other MSMEs in similar challenges in the future.